2020
DOI: 10.21203/rs.3.rs-40115/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yoga Practice Among Ethnically/Racially Diverse Emerging Adults: Associations with Body Image, Mindful and Disordered Eating, and Muscle-Enhancing Behaviors

Abstract: Abstract Background: Yoga may be beneficial for young people at risk for body dissatisfaction and unhealthy behaviors aimed at changing one’s body shape and size. This study explores associations between yoga practice and body image, mindful eating, disordered eating, and muscle-enhancing behaviors among a population-based sample of emerging adults from diverse socio-economic and ethnic/racial backgrounds.Methods: Survey dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Participants in the C-EAT (COVID-19 Eating and Activity over Time) study were members of the EAT 2010–2018 longitudinal study cohort who were invited to complete an online survey in 2020 during the U.S. outbreak of COVID-19. Participants included young people who attended middle schools and high schools in Minneapolis-St. Paul, Minnesota in 2009–2010 and were followed over time [ 13 , 14 , 15 ]. The C-EAT survey was designed to capture changes in weight-related health and markers of psychosocial well-being during COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…Participants in the C-EAT (COVID-19 Eating and Activity over Time) study were members of the EAT 2010–2018 longitudinal study cohort who were invited to complete an online survey in 2020 during the U.S. outbreak of COVID-19. Participants included young people who attended middle schools and high schools in Minneapolis-St. Paul, Minnesota in 2009–2010 and were followed over time [ 13 , 14 , 15 ]. The C-EAT survey was designed to capture changes in weight-related health and markers of psychosocial well-being during COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…In turn, yoga enhances body functionality, appreciation and embodiment, reducing self-objectification and body control by promoting body acceptance, self-compassion, and a sense of personal agency (Cox & Tylka, 2020). These competencies are fundamental in preventing and treating ED (Neumark-Sztainer et al, 2020). A systematic review of body-oriented therapies in ED prevention demonstrated that programmes engaging the body effectively reduce risk factors and promote protective factors.…”
Section: General Conclusionmentioning
confidence: 99%